(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The brief investigation focuses on the impact of the goniometer that is android goniometer or traditional goniometer.Which formerly check the degree of motion of the joints. Which eventually results in the more accurate and easy use of goniometer. To determine the joint mobility . Physical therapists routinely utilize goniometers to assess range-of-motion (ROM) in the musculoskeletal system. These measureshave been utilized to aid in the treatment and to evaluate therapeutic performance. Smartphone-based apps for sensing joint angles and movement are being investigated using newly developing technology.(1)The traditional goniometer is a typical technique for evaluating the degree of movement . Also it possibly have various limitations, such as the physician’s participation of both hands, this leads to hand instability and inaccuracy. Because of their ease of use, smartphones are becoming extremely popular.(2)According to the study, two very different approaches can be used to identify Full range of motion and also the variation in information taken by methods is less than 3.4 percent.(3)